2006
DOI: 10.1007/s11430-006-8262-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness length dynamic over several different surfaces and its effects on modeling fluxes

Abstract: Roughness length and zero-plane displacement over three typical surfaces were calculated iteratively by least-square method, which are Yucheng Experimental Station for agriculture surfaces, Qianyanzhou Experimental Station for complex and undulant surfaces, and Changbai Mountains Experimental Station for forest surfaces. On the basis of roughness length dynamic, the effects of roughness length dynamic on fluxes were analyzed with SEBS model. The results indicate that, aerodynamic roughness length changes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…Although our sensitivity analysis indicated that errors within the SEBS led to estimated H values with deviations (˘25%) of z 0m that were smaller than those for LST and air temperature, a 50% deviation in the parameterization of z 0m , as well as forest height, can generate errors of more than 40% for the H estimation. The result is consistent with those presented by van der Kwast et al [50], Zhou et al [75], and Ma et al [79]. In particular, according to the study of Zhou et al [71], the annual maximum effect of the roughness length dynamic on sensible heat flux was 33.80% and 18.11% for the Qianyanzhou (with a 11-12 meter high artificial needle forest) and Changbai Mountains (with a 26 meter high natural mixed forest) experimental stations, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although our sensitivity analysis indicated that errors within the SEBS led to estimated H values with deviations (˘25%) of z 0m that were smaller than those for LST and air temperature, a 50% deviation in the parameterization of z 0m , as well as forest height, can generate errors of more than 40% for the H estimation. The result is consistent with those presented by van der Kwast et al [50], Zhou et al [75], and Ma et al [79]. In particular, according to the study of Zhou et al [71], the annual maximum effect of the roughness length dynamic on sensible heat flux was 33.80% and 18.11% for the Qianyanzhou (with a 11-12 meter high artificial needle forest) and Changbai Mountains (with a 26 meter high natural mixed forest) experimental stations, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Abiding by the theories of EB, bulk atmospheric similarity (BAS) [68] and MOS [39], based on a combination of physical land surface parameters obtained from remote sensing data and meteorological forcing data, the SEBS has been proven to be a reliable remote sensing-based ET model in numerous studies conducted over multiple ecosystems and under various climate and landscape conditions [69][70][71][72][73][74]. However, few studies have focused on forests [75][76][77], especially those located in cold and arid regions.…”
Section: The Surface Energy Balance System (Sebs)mentioning
confidence: 99%
“…However, z om has larger short-term fluctuations at QYZ than at CBS. At CBS, one of the major drivers of large seasonal variations in z om is the distinct seasonal pattern of the LAI, which increases from a minimum at the beginning of the growing season (early May) to a maximum in late June and starts to decrease in the middle of September (Zhou et al 2006). The seasonal pattern of the 5-day mean of z om closely follows that of the LAI.…”
Section: Final Determination Of D and Z Ommentioning
confidence: 76%
“…This parameter also depends on the surface-air temperature difference and atmospheric conditions. Therefore, z om is affected by the integrated effects of aerodynamic and thermodynamic factors and rough elements, which means that z om is actually a parameter varying with wind speed, wind direction, terrain, atmospheric stratification, and LAI (Zhang et al 2004;Patil 2006;Zhou et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…L is used to determine the atmospheric stability near the surface [34]. When Z/L = 0, there is neutral stratification.…”
Section: Field Aerodynamic Roughness Length Calculationmentioning
confidence: 99%